Kebijakan Cina Melakukan Boikot Terhadap Ritel Fesyen Multinasional H&M Terkait Isu Perbudakan Kapas di Xinjiang - Novi Ratna Cahyani (Forum Kerjasama Pendidikan Tinggi, 2022)
Multinational fashion retailer H&M expressed concern over alleged forced labor carried out by China against ethnic Uighurs in the Xinjiang region. The Chinese government has repeatedly denied the allegations, but China's anger at H&M intensified after other countries sentenced China over the issue. Then the boycott policy was shown to H&M, which has contributed to the Chinese economy with its investment in more than 500 stores across China and as one of the major consumers of Chinese garment companies. This article aims to answer the question,